2017
DOI: 10.1128/iai.00507-17
|View full text |Cite
|
Sign up to set email alerts
|

Ready Experimental Translocation of Mycobacterium canettii Yields Pulmonary Tuberculosis

Abstract: Mycobacterium canettii, which has a smooth colony morphology, is the tuberculous organism retaining the most genetic traits from the putative last common ancestor of the rough-morphology Mycobacterium tuberculosis complex. To explore whether M. canettii can infect individuals by the oral route, mice were fed phosphate-buffered saline or 10 6 M. canettii mycobacteria and sacrificed over a 28-day experiment. While no M. canettii was detected in negative controls, M. canettiiinfected mice yielded granuloma-like l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Other prominent veterinary pathogens have been observed to be aerosolizable from an environmental source - Coxiella burnetii , which causes of Q Fever, has been observed to infect animals and humans exposed to contaminated wool ( 189 ) and Mycobacterium avium paratuberculosis , the causative agent in Johne’s Disease has been observed to be aerosolised in dust particles derived from bovine faecal material in animal housing ( 190 ). An intriguing recent study demonstrated that M. canettii , a pathogen predicted to be a common ancestor for the M. tuberculosis Complex, could produce pulmonary infection, indistinguishable from aerosol-mediated pulmonary infection, in mice fed spiked material ( 191 ).…”
Section: Climate and Environmentmentioning
confidence: 99%
“…Other prominent veterinary pathogens have been observed to be aerosolizable from an environmental source - Coxiella burnetii , which causes of Q Fever, has been observed to infect animals and humans exposed to contaminated wool ( 189 ) and Mycobacterium avium paratuberculosis , the causative agent in Johne’s Disease has been observed to be aerosolised in dust particles derived from bovine faecal material in animal housing ( 190 ). An intriguing recent study demonstrated that M. canettii , a pathogen predicted to be a common ancestor for the M. tuberculosis Complex, could produce pulmonary infection, indistinguishable from aerosol-mediated pulmonary infection, in mice fed spiked material ( 191 ).…”
Section: Climate and Environmentmentioning
confidence: 99%
“…Such a heterogeneous natural history of tuberculosis in neonates in the Lübeck series of cases may partly be explained by different gut microbiota maturation in the neonates [ 37 ]. Indeed, translocating M. canettii and M. tuberculosis has been shown to lead to both disseminating in the lymphatic and lung tissues after experimental gavage in mice [ 18 , 38 ]. It would be interesting to further document E. mundtii and E. casseliflavus interactions with M. tuberculosis in a mouse model, to observe interference with M. tuberculosis gut survival, translocation, and recirculation in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…canettii inoculation has demonstrated the potential of ingested M . canettii bacilli to relocate to lungs and other organs [8]. This experimental data supported that people could get infected with environmental M .…”
Section: Introductionmentioning
confidence: 63%